2013
DOI: 10.1371/journal.pone.0077781
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Hydrophobic Cavities in Allosteric Regulation of Formylglycinamide Synthetase: Insight from Xenon Trapping and Statistical Coupling Analysis

Abstract: Formylglycinamide ribonucleotide amidotransferase (FGAR-AT) is a 140 kDa bi-functional enzyme involved in a coupled reaction, where the glutaminase active site produces ammonia that is subsequently utilized to convert FGAR to its corresponding amidine in an ATP assisted fashion. The structure of FGAR-AT has been previously determined in an inactive state and the mechanism of activation remains largely unknown. In the current study, hydrophobic cavities were used as markers to identify regions involved in domai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 44 publications
(59 reference statements)
0
28
0
Order By: Relevance
“…All the proteins were expressed and purified by the previously described procedure. 27 X-ray Crystallography. Diffraction data for V333I were collected on Rigaku FR-E+ super bright microfocus rotating anode at the National Institute of Immunology (Delhi, India).…”
Section: ■ Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All the proteins were expressed and purified by the previously described procedure. 27 X-ray Crystallography. Diffraction data for V333I were collected on Rigaku FR-E+ super bright microfocus rotating anode at the National Institute of Immunology (Delhi, India).…”
Section: ■ Experimental Methodsmentioning
confidence: 99%
“…Previously, the first transition was attributed to the unfolding of the N-terminal domain. 27 Hence, it appears that the mutation of S312F causes conformational frustration of phenylalanine residue, forcing it to adopt a rotamer that pushes the N-terminal domain outward, resulting in partial unfolding of this region, thereby yielding a lower ellipticity value. The slight rearrangement of the Nterminal domain may also lead to opening of path 3, and catalysis is therefore unaffected.…”
mentioning
confidence: 99%
“…Amplified genes were ligated into pET-28a by using Kpn I and Bam HI restriction site and into modified versions of pET vector by using Bam HI, and Xho I restriction site. All mutants were transformed, then expressed in BL21_(DE3) cells, and finally purified as described previously (36). In brief, the starter culture was made by adding a single colony from transformed plasmid in BL21_(DE3) cells, grown overnight at 37°C, in 10 ml of LB media containing kanamycin (35 l/ml).…”
Section: Cloning Expression and Purificationmentioning
confidence: 99%
“…To determine the secondary structure content of various PurL mutants, a JASCO J-815 circular dichroism (CD) spectrometer was used. A 3.5 M concentration of all the mutants (in phosphate buffer containing 50 mM sodium phosphate, 50 mM NaCl) was used for recording the spectra as reported previously (36). Scans were performed at 25°C using 0.1-mm path length quartz cuvette at a differential integration time of 8 s with a scan rate of 50 nm/min.…”
Section: Spectroscopymentioning
confidence: 99%
“…Statistical Coupling Analysis (SCA) 30 applies principal component analysis to a multiple sequence alignment (MSA) covariance matrix to identify groups of "coevolving protein sectors" 31 that are believed to arise from selection acting upon protein functional properties 32 . SCA has been used to predict hydrophobic cavities 33 and surface sites 34 involved in allosteric regulation and to design proteins 35 . However, most published SCA studies identify a single sector, for which, it has been suggested 36 , statistically equivalent predictions may be made using sequence conservation alone.…”
mentioning
confidence: 99%